The identification of the difficulties in solving mathematical problems of junior high school mathematics teachers in Nusa Tenggara Timur and Maluku Utara - Heri Retnawati; Dhoriva Urwatul Wutsqo; Endang Listyani; Kartiko Rachman Y Prasetya (LPPM UNY, 2014)
This study aims to determine the difficulties in solving mathematical problems of junior high school mathematics teachers in Nusa Tenggara Timur and Maluku Utara, two of the 33 provinces in Indonesia. The method used in this study was descriptive exploratory. The data analysis was based on 114 junior high schools mathematics teachers’ responses to the five items of the National Examination questions. The items were the most difficult items according to the students, particularly those of the junior high schools in Nusa Tenggara Timur and Maluku Utara, whose graduation has not reached 100%. The result of the analysis indicated that the order of teachers’ difficulties in solving mathematical problems is executing the problem solving plan, understanding the problems, interpreting the results and designing the problem solving plan. Based on this study, 46.491% teachers had difficulty in executing the problem solving plan, 45.846% in understanding the problem, 43.129% in interpreting the results and 33.063% in designing the problem solving plan.